Sosialisasi Tata Kelola Dana Bantuan Sosial Masyarakat Serta Aksi Bebrbagi Jumat Berkah - Purwanti, Purwanti; Nurfitriani, Nurfitriani; Zilfana, Zilfana; Aidhi, Akhmad Al; Verahastuti, Camelia; Seftianur, Muh Achzani; Putri, Melisya (TAAWUN, 2023)
Social assistance (Bansos) has received great attention from many parties because many are interested in the existence of social assistance itself. The process of budgeting, evaluation, and monitoring must be carried out in a transparent and accountable manner as part of the administration of social assistance funds so that the public is aware of the methods used by the government or the agency managing these funds. The problems faced in managing social assistance funds accountable and transparently are at the neighborhood level (RT). Where not all RT administrators are able to provide financial reports on proper management of funds according to accounting principles. The purpose of this research is through this activity, to prove the effect of transparency, competence, internal control system, and organizational commitment. The method we use is the method of implementation in this socialization activity is lecture, question and answer and discussion. The participants in this service are the people in Rt. 34 Kelurahan Sambutan, Sambutan Subdistrict, Samarinda City was attended by 85 people and the result of this service was the administrators of Rt. 34 Kelurahan Sambatan Sambutan Sub-District Samarinda City has understood the concept of managing social assistance funds in an accountable and transparent manner and compiled the financial reports even better so as to increase the trust of the local community.